A Preliminary Study on the Qualitative and Quantitative Changes of Amino Acids in Whole Apple, Apple Peel, and Flesh Samples Grown in Lithuania - Aurita Bračiulienė; Vaidotas Žvikas; Mindaugas Liaudanskas; Valdimaras Janulis (Plants)
Amino acids are vital gradient compounds involved in protein synthesis and the regulation of physiological functions. Ten essential amino acids cannot be produced endogenously and must be obtained through dietary sources of animal or plant origin. Apples are among the most widely consumed fruits globally and contain not only vital nutrients such as carbohydrates, fatty acids, organic acids, and amino acids but also a rich variety of bioactive compounds, including flavonoids and phenolic and triterpenic acids. Due to their diverse range of health-promoting compounds, apples could serve as a potential plant-based source of amino acids. Scientific literature provides fragmented data describing the qualitative and quantitative variation of amino acid composition in apples and their different parts. The purpose of this study was to determine the variation in the qualitative and quantitative composition of amino acids in whole apples, as well as in their peel and flesh samples, grown under Lithuanian climatic conditions. This study investigated 10 different apple cultivars, grown in Lithuania. A total of 15 free amino acids were identified using the UHPLC–MS/MS methodology, including 7 essential and 8 nonessential amino acids. In the apple sample, the predominant amino acid was aspartic acid (Asp). The highest content of Asp was found in apple flesh (742.73 ± 37.14 μg/g dw, p < 0.05), followed by whole apple (705.32 ± 35.27 μg/g dw, p < 0.05), and apple peel (370.78 ± 18.54 μg/g dw, p < 0.05) samples of the ‘Lodel’ cultivar. The distribution of total amino acid content (TAAC) in different apple parts is presented in descending order: apple flesh > whole apple > apple peel. The Lithuanian apple cultivars—‘Alva’ (547.26 ± 27.36 μg/g dw–998.13 ± 49.91 μg/g dw), ‘Lodel’ (561.85 ± 28.09 μg/g dw–954.24 ± 47.62 μg/g dw), and ‘Rubin’ (132.92 ± 6.65 μg/g dw–835.08 ± 41.75 μg/g dw)—were identified as those that accumulated the highest TAAC in their fruit samples.